Rezension von: Islamist opposition in authoritarian regimes: the Party of Justice and Development in Morocco - Roussellier, Jacques (The Middle East journal, 2012)
Rezension von: Wegner, Eva: Islamist opposition in authoritarian regimes: the party of justice and development in Morocco. - Syracuse/N.Y. : Syracuse Univ. Press, 2011.‡‡